Pakistan against the Taliban: Wave of arrests weakens Afghan insurgents, but still doesn't signal strategic shift - Guido Steinberg; Christian Wagner; Nils Wörmer (Stiftung Wissenschaft und Politik (SWP), 2010)
Since January 2010, Pakistani security forces have arrested nearly a dozen leading figures of the Afghan Taliban. While these arrests have dealt a serious blow to the Taliban, Pakistan's leadership has not made any fundamental changes to its policy for dealing with insurgents. Pakistan still clings to its objective of exercising significant influence on Afghanistan's political fortunes and will continue to look to elements within the Taliban as an ends to fulfilling this objective. Current actions should be seen as more of a reaction to changes in the larger political situation. Pressure has long been placed on Islamabad by the USA to finally take effective action against the Afghan Taliban and al-Qaeda in Pakistan. At the same time, Pakistan's military leadership wants to participate in talks that are currently being conducted with the Taliban and therefore also presents itself as willing to cooperate. The arrests have caused shifts within the Taliban's internal power structure, which also has an impact on the situation in Kunduz and German troops in Afghanistan
Keywords: 320